Effect of Mileage Variation on Learning Outcomes of SMKN Students in Tangerang City, Banten Province - Kurniawan, Muhamad; Ira Megawati Gunawan Putri (Balai Diklat Keagamaan Ambon, 2023)
This study aims to describe the spatial patterns of variations in students' distance to school and to understand the effect of students' distance to school on student learning outcomes using quantitative descriptive research methods with a spatial approach. Based on the results of the study on variations in the distance traveled by students who fall within the range of 1,000 – 5,000 meters, only 57.82% of the total 11th-grade students are sampled. These results show that 42.18% of students cover a distance of more than 5,000 meters to reach schools from the data processing of the distance to school correlation test with the results of learning vocational subjects in class 11 odd semesters, it was found that the results of the linearity test had a Sig value. 0.04 or Sig. < 0.05, the relationship between the variables in this analysis is negative, the closer the distance students travel, the learning outcomes will have a high value.